Effect of interleukin-17A inhibitor in Japanese patients with psoriatic arthritis compared with tumor necrosis factor-alpha inhibitor. (29th April 2021) - Izumiyama, Takuya; Mori, Yu; Oizumi, Itsuki; Hamada, Soshi; Kurishima, Hiroaki; Terui, Hitoshi; Omori-Shimada, Ryoko; Yamasaki, Kenshi; Itoi, Eiji
Objectives: The patient of severe psoriatic arthritis (PsA) is mainly treated with oral methotrexate, ciclosporin, and anti-tumor necrosis factor-alpha inhibitors (TNFi). Recently, anti-interleukin-17A inhibitors (IL-17Ai) have been used in the treatment of PsA. This study aimed to evaluate the efficacy and safety of IL-17Ai in Japanese patients with PsA compared with those of TNFi. Methods: This was a longitudinal and retrospective study. The study population included 31 Japanese patients with PsA. All enrolled patients fulfilled the Classification Criteria for Psoriatic Arthritis. All patients were treated with TNFi or IL-17Ai. The assessed clinical manifestations were C-reactive protein (CRP)-based Disease Activity Score in 28 Joints (DAS28-CRP), disease activity in psoriatic arthritis (DAPSA), 20% achievement of American College of Rheumatology core set, swollen joint count (SJC), tender joint count (TJC), and visual analog scale (VAS). Functional ability of patients with PsA was analyzed using the modified health assessment questionnaire (mHAQ) score. We evaluated the parameters at baseline and weeks 12, 24, and 52. Results: The change in SJC, TJC, VAS, mHAQ, and DAPSA had no significant difference at weeks 12, 24, and 52. The improvements of CRP and DAS28-CRP were significantly higher in TNFi group only at week 12. The biologics retention rate was significantly higher in TNFi group by the log-rank test. No critical adverse events occurred. Conclusions: Our study presented that IL-17Ai had treatment effects comparable to TNFi. IL-17Ai might have the potential to become an alternative to the previous drug, but more large-scale studies are expected.